Variant morphology at martensite formation in shape memory CuAlNi alloys - Aydogdu, Y; Aydogdu, A; Atici, Y; Adiguzel, O (Iop Publishing Ltd, 1998)
[Abstract Not Available]
14th International Congress on Electron Microscopy -- AUG 31-SEP 04, 1998 -- CANCUN, MEXICO